Frequency and characterization of self-medication for dental manifestations in patients attending private clinics in Lima in 2021 - Arriarán Cisneros, Aristides (2022)
Introduction: The self-medication is the use of drugs without health professionals’ prescription that many times, instead of helping, aggravate the patient's health. Dental pain is the main reason for performing this act in the area of odontology. It is important to know if patients self-medicate in order to develop strategies to reduce the misuse of drugs and avoid this practice. Objective: Establish the frequency and characterization of self-medication in patients who visit to the three private dental clinics between the months of march to July in the year 2021. Materials and methods: Cross-sectional observational study with a sample of 450 patients from three dental clinics in the city of Lima. The assessment tool was a 13-question quiz about the main characteristics of self-medication. Results: The 85,8% of patients use drugs without medical prescription. 41.5% of the patients self-medicated did it with old prescriptions made by the dentist. The age group that more self-medicated was 26-35 years old with 35.5%. The most frequent type of disease was dental pain with 45.6%, The degree of instruction with the highest percentage was complete university superior with 32.9%. Conclusions: The frequency of self-medication of the patients who visited the three dental centers is considerably high.